Tri‐Coordinated Boron Species in Confined Boron Oxide Catalysts for Enhanced Low‐Temperature Oxidative Dehydrogenation of Propane - Zheng, Yuenan; Chen, Weixi; Liu, Zhankai; Lu, Wen‐Duo; Li, Wen‐Cui; Wang, Dongqi; Lu, An‐Hui (Angewandte Chemie International Edition, 2025)
Boron‐based catalysts exhibit great potential for oxidative dehydrogenation of propane (ODHP) to produce olefins. The straightforward synthesis of confined boron‐based catalysts commonly using H3BO3 is intractable because of its abundant hydroxyl groups easily interacting with the supports in a spatially nonselective manner. Herein, we managed to construct a confined BOx@SiO2 catalyst showing an impressive low‐temperature (400 °C) activity. This catalyst was prepared via the encapsulation of BN nanosheets by SiO2 shell and subsequent oxidization steps. The in situ generated boron–oxygen species were anchored to silica shells via B─O─Si and hydrogen bonds. BOx@SiO2 exhibited a unique catalytic behavior of propane conversion uprush, increasing from 5.3% at 410 °C to 28.4% at 424.6 °C for ODHP reaction. That was attributed to the efficient activation of propane triggered by the newly formed tri‐coordinated B─OH (B[3]a and B[3]b) active sites from the dispersion of molten BOx species in confined SiO2. Ab initio molecular dynamics (AIMD) simulations revealed that in the confined structure, the bond angles of O─B─O and B─O─B and system disorder of BOx species increased significantly in molten state, favoring the dispersion of BOx species and formation of B─OH groups, which drove the uprush of propane conversion. The confined BOx@SiO2 with highly dispersed BOx species was synthesized by the in situ transformation of BN@SiO2, which showed a remarkable activity of a unique C3H8 conversion uprush increasing from 5.3% at 410 °C to 28.4% at 424.6 °C for oxidative dehydrogenation of propane. The key for the efficient C3H8 activation was the increased amount of tri‐coordinated B─OH derived from the dispersion of molten BOx species within spatially confined SiO2.